2004
DOI: 10.1002/bdd.409
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of clarithromycin in rats with acute renal failure induced by uranyl nitrate

Abstract: In rats pretreated with dexamethasone (an inducer of CYP3A1/2 in rats) and troleandomycin (an inhibitor of CYP3A1/2 in rats), the area under the plasma concentration-time curve from time zero to time infinity (AUC) values of clarithromycin were significantly smaller (365 compared with 600 micro g min/ml) and greater (1410 compared with 581 micro g min/ml), respectively, than those in control rats. This indicated that clarithromycin was metabolized via CYP3A1/2 in rats. The expression of CYP3A1(23) increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…It has been reported that CYP3A1 (23) is involved in the metabolism of clarithromycin in rats (14). Hence, it would be expected that pharmacokinetics of clarithromycin could be changed in rats with DMIA and DMIS due to an increase in the expression and mRNA level of CYP3A1(23) levels in the rats.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that CYP3A1 (23) is involved in the metabolism of clarithromycin in rats (14). Hence, it would be expected that pharmacokinetics of clarithromycin could be changed in rats with DMIA and DMIS due to an increase in the expression and mRNA level of CYP3A1(23) levels in the rats.…”
mentioning
confidence: 99%
“…Hence, it would be expected that pharmacokinetics of clarithromycin could be changed in rats with DMIA and DMIS due to an increase in the expression and mRNA level of CYP3A1(23) levels in the rats. The purpose of this study is to report the pharmacokinetic changes after intravenous and oral administration of clarithromycin at a dose of 20 mg/kg of body weight to rats with DMIA and DMIS in relation to CYP3A1(23) changes.Chemicals (1,14), the methods of induction of diabetes mellitus by alloxan (12,20) or streptozotocin (21), pretreatment and surgical procedures for intravenous and oral administration (1, 14), procedures for intravenous (n ϭ 12 and 11 for rats with DMIA and their control rats, respectively, and n ϭ 8 and 7 for rats with DMIS and their control rats, respectively) and oral (n ϭ 9 and 11 for rats with DMIA and their control rats, respectively, and n ϭ 10 and 9 for rats with DMIS and their control rats, respectively) studies (1,14), and high-performance liquid chromatography analysis of clarithromycin (1,14) were similar to previously reported methods. The procedures for the measurement of the maximum rate of metabolism (V max ), K m , and the intrinsic clearance (CL int ) for the disappearance of clarithromycin in hepatic microsomal fractions were similar to previously reported methods (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers of male rats used were 8, 8 and 7 for control rats and rats pretreated with oxolamine at doses of 10 and 50 mg/kg, respectively, for phenytoin, and the corresponding values for torasemide and clarithromycin were 9, 10 and 10, and 8, 9 and 10. The blood sampling time schedules for phenytoin [11], torasemide [12] and clarithromycin [13] were the same as previously reported methods. The other procedures were similar to the above mentioned warfarin studies.…”
Section: Animalsmentioning
confidence: 99%
“…On day 4 just after oral administration of oxolamine, phenytoin (at a dose of 25 mg/kg; dissolved in distilled water with a minimum amount of 10 n NaOH), mainly metabolized via CYP2B1 in rats [11], torasemide (at a dose of 2.5 mg/kg; dissolved in distilled water with a minimum amount of 10 n NaOH and adjusted to a final pH of approximately 8 with Tris-HCl), mainly metabolized via CYP2C11 in rats [12], or clarithromycin (at a dose of 20 mg/kg; dissolved in 0.9% NaCl-injectable solution by adding few drops of 85% phosphoric acid), mainly metabolized via CYP3A2 in rats [13] was infused (total injection volume of 2 ml/kg for each drug) for 1 min via the jugular vein of male rats. The numbers of male rats used were 8, 8 and 7 for control rats and rats pretreated with oxolamine at doses of 10 and 50 mg/kg, respectively, for phenytoin, and the corresponding values for torasemide and clarithromycin were 9, 10 and 10, and 8, 9 and 10.…”
Section: Animalsmentioning
confidence: 99%